GABAA receptor expression and white matter disruption in intrauterine growth restricted piglets - Viskasari Pintoko Kalanjati (Elsevier, Wiley, 2017)
Intrauterine growth restriction (IUGR) is one of the most common causes of perinatal mortality and morbidity. White matter and neuronal injury are major pathophysiological features of the IUGR neonatal brain. GABAA (γ‐aminobutyric acid type A) receptors have been shown to play a role in oligodendrocyte differentiation and proliferation in the neonatal brain and may be a key factor in white matter injury and myelination in IUGR neonates. Whether there are impairments to the GABAergic system and neuronal cytoskeleton in IUGR brain has yet to be elucidated. This study aims to examine GABAA receptor α1 and α3 subunit protein expression and distribution in parietal cortex and hippocampus of the IUGR piglet at four different ages (term = 115 d – days gestational age), 100 d, 104 d, birth (postnatal day 0–P0) and P7 and to examine neuronal and myelination patterns. Significant alterations to GABAA receptor α1 and α3 protein expression levels were observed in the IUGR piglet brain of P7 IUGR piglets with significantly greater α3 expression compared to α1 expression in the hippocampus while there was virtually no difference between the two subunits in the parietal cortex. However a significantly lower α1/α3 ratio was evident in P7 IUGR cortex when compared with P7 NG cortex. Neuronal somatodendrites studied using MAP2 immunohistochemistry showed reduced and disrupted somatodendrites while MBP immunolabelling showed loss of axonal fibres from gestational day 104 d through to P7. These findings provide insights into the effects of IUGR on the development of the GABA system, altered developmental maturation of GABAA receptor subunit expression in the IUGR brain may influence myelination and may partly explain the cognitive disabilities observed in IUGR. Understanding the mechanisms behind grey and white matter injury in the IUGR infant is essential to identifying targets for treatments to improve long‐term outcomes for IUGR infants.